Triazole-functionalised and polymer-supported phenylboronic acid catalysts for direct amidation of carboxylic acids at room temperature. - Mafaune, Asslly Tafara (Stellenbosch : Stellenbosch University, 2023)
Thesis (PhD)--Stellenbosch University, 2023.